2015
DOI: 10.1364/ol.40.001101
|View full text |Cite
|
Sign up to set email alerts
|

65 W ZnGeP_2 OPO directly pumped by a Q-switched Tm^3+-doped single-oscillator fiber laser

Abstract: An efficient actively Q-switched Tm3+-doped single-oscillator fiber laser based on a silica polarization-maintaining (PM) double-clad fiber provided average powers of 23 W at pulse widths of 65 ns at 40 kHz pulse repetition frequency. It was used to directly pump a ZnGeP2 optical parametric oscillator (OPO). Up to 6.5 W were generated in mid-IR wavelength range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 11 publications
3
15
1
Order By: Relevance
“…Direct fiber pumping of ZGP mid-IR OPO using pump lasers built in a master oscillator power-amplifier configuration has been already successfully demonstrated reaching maximum 3 W of mid-IR output power [16], [17] and [18]. We have recently reported (to the best of our knowledge) the highest ever demonstrated mid-IR output power, 6.5 W, from a Tm 3+ -doped fiber single oscillator laser pumped ZGP OPO [9] and the first OP-GaAs OPO pumped by a 2.09 μm Q-switched Tm 3+ ,Ho 3+ :silica fiber laser [10], [11].…”
Section: Nonlinear Crystals Direct Fiber-pumpingmentioning
confidence: 86%
See 1 more Smart Citation
“…Direct fiber pumping of ZGP mid-IR OPO using pump lasers built in a master oscillator power-amplifier configuration has been already successfully demonstrated reaching maximum 3 W of mid-IR output power [16], [17] and [18]. We have recently reported (to the best of our knowledge) the highest ever demonstrated mid-IR output power, 6.5 W, from a Tm 3+ -doped fiber single oscillator laser pumped ZGP OPO [9] and the first OP-GaAs OPO pumped by a 2.09 μm Q-switched Tm 3+ ,Ho 3+ :silica fiber laser [10], [11].…”
Section: Nonlinear Crystals Direct Fiber-pumpingmentioning
confidence: 86%
“…For example, in band II, up to 6.5 W of averaged power was obtained from a ZGP OPO pumped by a Tm 3+ -doped fiber laser [9]. At 40 kHz repetition rate, the pulse duration was around 65 ns at the maximum output power.…”
mentioning
confidence: 99%
“…The most challenging component of the system is the efficient 2 µm pulsed laser. Both bulk Ho lasers and Ho fiber lasers allowing Q-switched operation with high pulse energies can be suitable for pumping a ZGP OPO or OPA [12][13][14] . The second challenge is to reduce the effect of the feedback from the OPO or the OPA into the pump laser and the risk of the damage to the mirror or medium coating and the nonlinear medium.…”
Section: Introductionmentioning
confidence: 99%
“…The output power and pulse energy in passive modulation techniques from single oscillators are limited, on one hand, to a certain output power level for stable operation, and on the other hand, by the damage threshold of the available modulators. Single oscillator actively Qswitched fiber sources emitting around 2 µm have been already successfully demonstrated by directly pump Tm 3+ -doped or Tm 3+ , Ho 3+ -codoped silica fibers with 793 nm high power diodes [14][15][16][17]. In [14][15][16], nanosecond pulses around 2 µm have been generated at tens of kilohertz of repetition rates, with average output powers reaching a maximum of 25 W. Further power scaling of these fiber lasers were limited by thermal-induced damaging observed on both uncooled fiber tips.…”
Section: Introductionmentioning
confidence: 99%
“…Single oscillator actively Qswitched fiber sources emitting around 2 µm have been already successfully demonstrated by directly pump Tm 3+ -doped or Tm 3+ , Ho 3+ -codoped silica fibers with 793 nm high power diodes [14][15][16][17]. In [14][15][16], nanosecond pulses around 2 µm have been generated at tens of kilohertz of repetition rates, with average output powers reaching a maximum of 25 W. Further power scaling of these fiber lasers were limited by thermal-induced damaging observed on both uncooled fiber tips. Stutzki et al [17] demonstrated a 15 ns single pulse operation with a maximum average output power of 39 W at 14 kHz repetition rate around 1.9 µm.…”
Section: Introductionmentioning
confidence: 99%